The Effect of Liquidity and Profitability on Company Value: Study on Cement Companies Listed on The Indonesia Stock Exchange For The 2016-2020 Period - Novia Halimatus Sa’diah; Ester Manik; Windi Matsuko Danasasmita (Center of Research, STIE Pasundan, Bandung, Indonesia., 2023)
This research determines the effect of liquidity, namely the current ratio, and profitability, return on assets to the company's value, namely price to book value in the Cement Sub-Sector Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2020 period. The sampling technique used in this research is purposive sampling. The analysis technique used is multiple linear regression, coefficient of determination, and partial and significance tests. We are processing research data using the SPSS 25 program. Based on the results of the study and the calculation value of r square of 0.501 or equal to 50.1%, this figure means that the liquidity variable (CR) (X1) and profitability variable (ROA) (X2) simultaneously (together) influence the variable. The firm value (Y) is 50.1%, while other variables outside this regression equation or unexamined variables influence the remaining 49.9%.